EPCO-10. SYSTEMS BIOLOGY-BASED THERAPEUTIC PREDICTIONS WITH GBMSYGNAL AND CLINICAL CORRELATES IN THE REAL-WORLD LONGITUDINAL OUTCOMES REGISTRY XCELSIOR. (14th November 2022) - Stuhlmiller, Timothy; Turkarslan, Serdar; Friedland, Julie; Shapiro, Mark; Kesari, Santosh; Patel, Anoop; Baliga, Nitin
Abstract: Glioblastoma is an aggressive disease with multiple disrupted signaling networks in the same tumor, demanding the development of personalized combination regimens. Using SYstems Genetics Network AnaLysis we analyzed TCGA multiomics datasets for 422 glioblastoma patients to generate a predictive disease network model (gbmSYGNAL). This model seeks to uncover how subsets of mutations causally modulate regulators (transcription factors, miRNAs, etc.) that mechanistically regulate gene modules ("regulons") associated with disease progression. Using the real-world registry XCELSIOR (NCT03793088), we identified 55 anti-cancer therapies utilized in glioblastoma treatment (N = 354 patients) and associated them with positive or negative regulon activity within individual patients across the TCGA cohort. A median of 12 regulons were targeted by each drug. Interestingly, nilotinib targeted only 5 regulons but they were found to be active in 38% of patients and regulons overactive in >35% of patients were targeted by repurposed anti-cancer drugs including celecoxib, hydroxychloroquine, and tocilizumab. Standard-of-care treatments lomustine and bevacizumab were predicted to be active in only 28% and 23% of patients, respectively. Using gbmSYGNAL, we then prioritized drugs for 12 additional patients from the XCELSIOR registry. Median overactive regulons per patient was 110 (range 55-254) represented by a median 28 molecular targets (range 17-37). Surprisingly, regulons targeted by metformin were predicted to be overactive in all patients. Certain regulons displayed a binary pattern (high "on" activity or completely "off" per patient) including those targeted by pemetrexed, pembrolizumab, and valproic acid while others showed a gradient of activity across patients including selinexor, panobinostat, palbociclib, and alpelisib. Systems biology analysis of commercially available NGS data combined with the XCELSIOR direct patient engagement platform yielded therapeutically actionable insights for glioblastoma patients in real time. Correlation with clinical outcomes is ongoing for 50 additional patients and will be presented at the meeting.